2007
DOI: 10.1039/b707507n
|View full text |Cite
|
Sign up to set email alerts
|

Bead-based immunoassays using a micro-chip flow cytometer

Abstract: A microfabricated flow cytometer has been developed for the analysis of micron-sized polymer beads onto which fluorescently labelled proteins have been immobilised. Fluorescence measurements were made on the beads as they flowed through the chip. Binding of antibodies to surface-immobilised antigens was quantitatively assayed using the device. Particles were focused through a detection zone in the centre of the flow channel using negative dielectrophoresis. Impedance measurements of the particles (at 703 kHz) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 34 publications
1
87
0
Order By: Relevance
“…Focusing original random distributed particles into one or several equilibrium positions can be used to enrich or separate particles according to their different equilibrium positions [1]. Also, focusing of particles along a specific path can be employed in flow cytometry for detection and enumeration of bio-particles [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing original random distributed particles into one or several equilibrium positions can be used to enrich or separate particles according to their different equilibrium positions [1]. Also, focusing of particles along a specific path can be employed in flow cytometry for detection and enumeration of bio-particles [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…1-3 Several microfluidic devices have recently been reported for single-cell impedance measurement using coplanar 41,42 and parallel [43][44][45][46][47] facing electrodes. Hydrodynamic trapping methods have been employed in conjunction with -EIS for measuring cellular impedance properties over extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…All of these devices were meant for counting and possibly sizing purposes. Only with the possibility to vary the impedance measurement frequency, however, was it demonstrated that the microfluidic approach has the potential for cell characterization (18,51,(69)(70)(71).…”
Section: Microfluidic Coulter Systems Sensitivitymentioning
confidence: 99%